Estudo do comportamento de materiais não convencionais utilizados como revestimento de paredes, visando à redução da carga térmica. - Sousa, Vívian Aparecida Lima (2012)
This dissertation studied the behavior thermal, physical and mechanical of mortar coatings composed of pure gypsum, plaster / EVA (ethylene-vinyl acetate copolymer) and gypsum / vermiculite applied on surfaces of building walls in order to reduce the thermal load on the walls consisted of conventional ceramic bricks and cement-sand mortar, taken as a reference. The objective was to obtain a material capable of reducing the thermal load and therefore the consumption of electrical energy used in air conditioning system for the thermal comfort of people and protection of equipment from the electrical substation of CHESF located in Milagres, in the semi-arid northeast of Brazil. The mortars were developed at the Laboratory for Testing Materials and Structures LABEME / UFPB, and underwent tests assessing their physical and mechanical properties. The result showed that the mortars have developed physical and mechanical properties that satisfy the standards in Brazil, being suitable the use of coating internal and external walls. Moreover, its application involves the reduction of non-degradable material released in nature, as the residue of EVA. The thermal conductivity of each mortar was obtained at the Laboratory of Porous Media and Thermophysical Properties LMPT UFSC-through flowmetric method. The mortar plaster, plaster / EVA and gypsum / vermiculite showed the thermal conductivity of 0.43 W / mK, 0.41 W / mK and 0.22 W / mK, respectively, behaving as thermal insulation. The results showed that the coating using mortar and plaster gypsum / EVA had a 18% reduction of thermal load of the environment on the wall by reference. And using the coating gypsum mortar / vermiculite this reduction reached 36%.